Late Tertiary Plant Macrofossils from Localities in Arctic/Subarctic North America: A Review of the Data - Matthews, Jr., John V.; Ovenden, Lynn E. (ARCTIC, 1990)
Bryophyte and vascular plant fossils occur at many late Tertiary sites in Alaska and northern Canada. A number of these floras are received here. The oldest flora, possibly of late Early Miocene age, is probably the one from the Mary Sachs gravel at Duck Hawk Bluffs, Banks Island. The youngest are of early Quaternary age. The floras are of several types. The youngest (Cape Deceit Formation) contains only plants that grow in the Arctic and Subarctic today. The Meighen Island Beaufort Formation contains a few extinct taxa (Aracites globosa) and fossil plants, such as Sambucus, Comptonia, and Physocarpus, that are not found in the present subarctic and arctic regions of North America. Some of these floras also contain fossils of a five-needle pine that may represent the Japanese Stone pine (Pinus pumila). A third group of floras, from Cone Bluff and Lava Camp, Alaska, usually contains more extinct plants (Epipremnum crassum, Decodon and cf. Paliurus) as well as fossils of pines in the subsection Cembrae. The Mary Sachs gravel flora, with taxa such as Metasequoia, Glyptostrobus, Taxodium, Juglans, and Liriodendron, stands apart from all three of the above-mentioned floral types. The Mary Sachs gravel flora represents mixed coniferous and hardwood forests. Most of the other floras represent coniferous forests that were floristically richer than present boreal forest. Some of the richness is due to taxa now found only in Eurasia. The Meighen Island Beaufort flora and some of those from the high-level alluvium on Ellesmere Island represent forest tundra. Several lines of evidence show that the Beaufort Formation on Meighen Island in the Canadian Arctic is about 3 million years old. Several of the younger floras contain abundant, well-preserved bryophyte fossils. Unlike the vascular plants, all of them represent extant species.